Case Study of Pseudomonas sp. in Giant Gourami (Osphronemus goramy) via Anatomical Pathology, Histopathology, and Microbiological Examinations, and Tetracycline Sensitivity Testing - Rahmaniar, Reina Puspita; Rahmawati, Indra; Nussa, Olan Rahayu Puji Astuti; Firmansyah, Muhammad Irwan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Pseudomonas sp. is an opportunistic bacterial pathogen causing systemic infections in cultured fish, resulting in economic losses and increasing concerns regarding antimicrobial resistance. However, comprehensive pathological and microbiological confirmation remains limited. This study aimed to evaluate Pseudomonas sp. infection in giant gourami (Osphronemus goramy) through pathological examination, bacterial identification, and antibiotic susceptibility testing. A descriptive case study was conducted on one naturally infected fish (code F-11). Clinical observation, necropsy, histopathological examination of the liver and gills using hematoxylin-eosin staining, bacterial isolation on MacConkey agar, Gram staining, biochemical characterization, and Kirby-Bauer disk diffusion testing with 30 μg tetracycline were performed. Data were analyzed descriptively by integrating pathological and microbiological findings. Gross examination revealed ecchymotic hemorrhages in the gills, labyrinth organ, and liver, hepatic nodules, and jejunal petechiae. Histopathology demonstrated congestion, inflammatory cell infiltration, hemorrhage, focal hepatic necrosis, epithelial desquamation, and lamellar necrosis in the gills. The isolate produced transparent non-lactose-fermenting colonies, consisted of Gram-negative rods, and exhibited biochemical characteristics consistent with Pseudomonas sp. The isolate remained susceptible to tetracycline, producing a 28-mm inhibition zone. These findings confirm Pseudomonas sp. infection and highlight the importance of integrated pathological and microbiological diagnosis to support appropriate antimicrobial therapy and antimicrobial resistance surveillance in aquaculture.